2000
DOI: 10.1038/sj.cgt.7700214
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity and safety of adenoviral vector-expressed wild-type p53 after intratumoral injection in melanoma and breast cancer patients with p53-overexpressing tumors

Abstract: p53 mutations are common genetic alterations in human cancer. Gene transfer of a wild-type (wt) p53 gene reverses the loss of normal p53 function in vitro and in vivo. A phase I dose escalation study of single intratumoral (i.t.) injection of a replication-defective adenoviral expression vector containing wt p53 was carried out in patients with metastatic melanoma or breast cancer with increased p53 protein immunoreactivity in pretreatment tumor biopsies. The biological activity of the injected wt p53 was assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…40 Even if a small amount of adenoviral vectors enter into circulation, the host immune response might be limited and does not seem to significantly reduce the effectiveness of readministration. 47,48 In this study, 5 courses of intra-tumoral delivery directed high-level expression of endostatin mRNA and protein inside NPC CNE-2 xenografted tumors, in association with significant inhibition of growth and angiogenesis. These results suggest that antiangiogenic therapy may be an important future addition to the multidisciplinary therapeutic approaches for NPC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…40 Even if a small amount of adenoviral vectors enter into circulation, the host immune response might be limited and does not seem to significantly reduce the effectiveness of readministration. 47,48 In this study, 5 courses of intra-tumoral delivery directed high-level expression of endostatin mRNA and protein inside NPC CNE-2 xenografted tumors, in association with significant inhibition of growth and angiogenesis. These results suggest that antiangiogenic therapy may be an important future addition to the multidisciplinary therapeutic approaches for NPC.…”
Section: Discussionmentioning
confidence: 83%
“…47 When delivered intra-tumorally, adenoviruses can direct tumor-specific, therapeutically relevant transgene expression and induce local immunotherapy for tumor cells. 40 Even if a small amount of adenoviral vectors enter into circulation, the host immune response might be limited and does not seem to significantly reduce the effectiveness of readministration.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it is noteworthy that p53 is among the principal mediators of the response to genotoxic stress and that many cancer therapeutic interventions, including ionizing radiation and chemotherapy, are predicated on the selective induction of genotoxic stress in cancer cells. Importantly, the feasibility of restoration of p53 function using adenoviral-mediated wt p53 gene transfer (Ad-p53) is currently being evaluated in clinical trials for patients with carcinoma of the lung (Swisher and Roth, 2002), prostate (Introgen, 2003), urinary bladder (Pagliaro, 2000), brain (Lang et al, 2003), breast (Dummer et al, 2000), ovary (Wen et al, 2003), and head and neck (Clayman et al, 1998(Clayman et al, , 1999. Upregulation of the antiapoptotic bcl-2 proto-oncogene is a common event in diverse malignancies including prostate cancer (MacCarthy-Morrogh et al, 1999;Moul, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple preclinical studies and clinical trials have demonstrated the therapeutic efficacy and minimal side effects of liposomal gene therapy for cancers. [5][6][7][8] The efficacy of gene therapy depends on the promoter activity. As breast cancer frequently develops metastasis, the new therapy should be designed for systemic administration.…”
Section: Introductionmentioning
confidence: 99%